Systematic review and meta-analysis of Chinese herbal formula Tongxie Yaofang for diarrhea-predominant irritable bowel syndrome: Evidence for clinical practice and future trials - Liang, Shi-Bing; Cao, Hui-Juan; Kong, Ling-Yao; Wei, Jia-Li; Robinson, Nicola; Yang, Si-Hong; Zhu, Si-Jia; Li, Yu-Qi; Fei, Yu-Tong; Han, Mei; Liu, Jian-Ping (Frontiers in Pharmacology, 2022)
Introduction: Diarrhea-predominant irritable bowel syndrome (IBS-D) significantly decreases the quality of life of patients and their families, and affects patients’ mental health. No specific western medications are available. Ancient classical Chinese medical texts have recognized Tongxie Yaofang (TXYF) as a therapy for diarrhea which is widely used in clinical practice. Standard TXYF prescription (S-TXYF) is composed of 4 herbal medicines : Atractylodes macrocephala Koidz. [Asteraceae; Rhizoma Atractylodis Macrocephalae.], Paeonia lactiflora Pall. [Ranunculaceae; Paeoniae Radix Alba], Citrus × aurantium L. [Rutaceae; Citri Reticulatae Pericarpium] and Saposhnikovia divaricata (Turcz. ex Ledeb.) Schischk. [Umbelliferae; Saposhnikoviae Radix]. This review aimed to evaluate the therapeutic effects and safety of S-TXYF for IBS-D. Methods: Eight English and Chinese electronic databases were searched from their inception to December 25, 2021 for randomized controlled trials (RCTs) comparing S-TXYF with placebo, western medications or no treatment for IBS-D. The primary outcome was the global improvement of IBS-D symptoms. Data were analyzed using Cochrane’s Revman 5.4 software. Evidence certainty was assessed using the online GRADEpro tool for the primary outcome. Results: Eleven RCTs involving 985 adults with IBS-D were included. For global improvement of symptoms, S-TXYF was superior to western medication and placebo (moderate evidence by GRADE). Regarding the improvement of stool consistency, stool frequency and abdominal pain, S-TXYF was significantly effective than placebo. In addition, S-TXYF was superior to western medication on improving the quality of life and relieving anxiety. Six trials reported adverse events: 5 of them reported (non-serious) adverse events occurred in both groups, and 1 trial reported that 3 cases with adverse events (constipation, elevation in liver-enzyme, nausea) occurred in S-TXYF group and 3 cases with adverse events (abdominal distension, nausea) occurred in placebo group. Conclusions: Although current results showed that S-TXYF may have potential to treat IBS-D and its use appears to be safe, no a clear and confirmed conclusion can be drawn from our review as the overall inadequate design of the included trials reviewed. So more rigorous trials are warranted to establish confirmed evidence on its benefits and safety.